Natural Compounds Synthesis: A Perspective of Modern Chemistry - Ortiz, Aurelio; Sansinenea, Estibaliz (Letters in Organic Chemistry, 2024)
Natural products have been created by nature and are derived from organisms such as plants or microorganisms. The natural compounds are isolated from natural sources in very small quantities, making it difficult for the form to achieve the compounds' good yields. The last is relevant for doing biological essays and chemical structure elucidation. Besides, they have diverse chemical structures, which have inspired organic chemists to do their organic synthesis. It is important to construct a strategy based on a well-designed retrosynthesis. The reproducibility of the selected methodology, the yields of the compounds of each step and stereoselectivity or diastereoselectivity of the reactions that are being used are the main key points to guarantee the success of a natural compound synthesis. Modern technologies can be the solution. In this review, we try to compile in the form of a critic perspective the most modern techniques that organic chemists are applying for the synthesis of complex natural compounds.
Keywords: retrosynthesis